Irish National Diabetic RetinaScreen Programme: report on five rounds of retinopathy screening and screen-positive referrals. (INDEAR study report no. 1). Issue 3 (17th December 2020) - Pandey, Rajiv; Morgan, Margaret M; Murphy, Colette; Kavanagh, Helen; Acheson, Robert; Cahill, Mark; McGettrick, Patricia; O'Toole, Louise; Hamroush, Fatima; Mooney, Therese; Byrne, Helen; Fitzpatrick, Patricia; et al.
Abstract : Objective: To study the uptake of annual diabetic retinopathy screening and study the 5-year trends in the detection of screen-positive diabetic retinopathy and non-diabetes-related eye disease in a cohort of annually screened individuals. Design: Retrospective retinopathy screening attendance and retinopathy grading analysis. Setting: Community-based retinopathy screening centres for the Diabetic RetinaScreen Programme. Participants: 171 557 were identified by the screening programme to be eligible for annual diabetic retinopathy screening. 120 048 individuals over the age of 12 consented to and attended at least one screening appointment between February 2013 to December 2018. Main Outcome Measures: Detection rate per 100 000 of any retinopathy, screen-positive referrable retinopathy and nondiabetic eye disease. Results: Uptake of screening had reached 67.2% in the fifth round of screening. Detection rate of screen-positive retinopathy reduced from 13 229 to 4237 per 100 000 screened over five rounds. Detection of proliferative disease had reduced from 2898 to 713 per 100 000 screened. Non-diabetic eye disease detection and referral to treatment centres increased almost eightfold from 393 in round 1 to 3225 per 100 000 screened. The majority of individuals referred to treatment centres for ophthalmologist assessment are over the age of 50 years. Conclusions: Screening programme has seen a reduced detection rate both screen-positive retinopathy referral in Ireland over five rounds of screening. Management of nondiabetic eye diseases poses a significant challenge in improving visual outcomes of people living with diabetes in Ireland.